Preparation and characterization of nanocapsules containing 2-nitrate and 1,3-diisobutoxypropane (NDIBP) nanocapsules and NDIBP/cyclodextrin inclusion complexes - Arruda, Ray Ravilly Alves; Vasconcelos, Ulrich; Travassos, Rafael de Almeida; Bonifácio, Tarcísio Tárcio Corrêa; Braga, Valdir de Andrade; Kretzschmar, Elisângela Afonso de Moura (Seven Editora, 2024)
2-nitrate-1,3-diisobutoxypropane (NDIBP) is a synthetic organic nitrate derived from glycerin, with low solubility in water. The objective of this work was to prepare and characterize inclusion complexes and nanocapsules with NDIBP. The inclusion complexes were prepared by lyophilization and the nanocapsules by the preformed polymer interfacial deposition method. The solubility isotherms determined for NDIBP showed Al-type profiles (K1:1 = 33.0 M-1). The formation of the inclusion complex provided a 12.5-fold increase in the solubility of NDIBP. The inclusion complexes showed changes in crystal structure and stability up to 150 days at 4ºC. The nanocapsules measured diameters between 100 and 300 nm, and exhibited polydispersion index below 0.2, and zeta potential < -30 mV. In addition, the nanosystems studied showed fungicidal and vasorelaxant activity of the mesenteric artery, thus showing that the nanotechnological strategies employed are promising in increasing desirable characteristics to the NDIPB. DOI:https://doi.org/10.56238/sevened2024.007-054